2022
DOI: 10.1155/2022/2448161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutritional Status of Intensive Care Unit COVID-19 Patients Based on the Nutritional Risk Screening 2002 Score

Abstract: Background. Patients with COVID-19 are susceptible to malnutrition, which is particularly concerning among critically ill patients. We evaluated the Nutritional Risk Screening 2002 (NRS-2002) score in such patients and determined its relationship with the hospitalization outcome. Methods. This cross-sectional study involved COVID-19 patients admitted to the intensive care units (ICUs) of Shahid Faghihi Hospital, Shiraz, Iran, between February and March 2021. We assessed the nutritional status using NRS-2002 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Several reviews have indicated the important roles of micronutrients in immune response [18,20,32,80,87,125], with these roles also applying to the treatment of COVID-19 [20,87,126,127]. Deficiencies of these micronutrients have been reported in increased infection and severity of COVID-19 [128][129][130][131][132].…”
Section: The Corona Virus Disease: Can Micronutrients Help?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews have indicated the important roles of micronutrients in immune response [18,20,32,80,87,125], with these roles also applying to the treatment of COVID-19 [20,87,126,127]. Deficiencies of these micronutrients have been reported in increased infection and severity of COVID-19 [128][129][130][131][132].…”
Section: The Corona Virus Disease: Can Micronutrients Help?mentioning
confidence: 99%
“…Vitamins C and D, zinc and selenium, which are essential micronutrients, have been reported to improve the treatment of COVID-19 and reduce mortality [128,133]. The effect of these micronutrients against COVID-19 is generally to strengthen the immune system by being available for every metabolic process.…”
Section: The Corona Virus Disease: Can Micronutrients Help?mentioning
confidence: 99%
“…There is already solid evidence supporting the use of specific protein-rich food nutrient supplements on COVID-19 patients’ morbidity and mortality [ 97 ]. In detail, in the literature, some reports evaluated the impact of nutrition in ICU COVID-19 patients with early manifestations of malnutrition and, sarcopenia [ 98 ]. It is important to recognize that both malnutrition/sarcopenia and hyper-inflammatory state are significantly associated with morbidity and mortality of COVID-19 patients [ 99 ] ( Figure 1 ).…”
Section: Gut Dysbiosis Modulation Through Probiotics and Immunonutritionmentioning
confidence: 99%
“…Moreover, Figure 2 shows all the curcumin RCTs in COVID-19, studying several other outcomes in addition to mortality (hospitalization, ventilation, numbers of recovery or recovery time, progression of the disease, oxigen saturation, viral positivity, in both early and late treatments): [17,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. This plot shows pooled effects, see the specific outcome analyses for individual outcomes, and the heterogeneity section [21] for discussion.…”
Section: Curcuminmentioning
confidence: 99%
“…Figure 2. Random effects meta-analysis for all RCTs about curcumin in COVID-19[17,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. This plot shows pooled effects, see the specific outcome analyses for individual outcomes, and the heterogeneity section[21] for discussion.…”
mentioning
confidence: 99%